THEORETICAL AND PRACTICAL ASPECTS OF POSSIBILITIES OF VISUALIZATION AND RECOVERY OF PAPILLAE PATTERN PRINTS FROM BIOLOGICAL SURFACES - Sīda, Raivo; Zīle, Aelita (Administrative and Criminal Justice, 2016)
The aim of the authors’ experiment conducted was to find out whether it is possible to find, visualise and recover papillae pattern prints from the surfaces of fruits, vegetables and plant leaves. The experiment was performed in four stages. The first stage was performed in the room where the temperature varied from 21°C to 25°C and the time periods were as follows: prints were visualised and copied immediately after leaving them, in 1 hour after leaving them, as well as in 24 hours, in 48 hours, in 72 hours and in 120 hours after leaving the prints. 217 papillae pattern prints were left on the surfaces of fruits and vegetables. 119 of them were recognised as valid for person identification. The second stage was performed under natural weather conditions with the air temperature from 14°C to –20°C. The fruits and vegetables were not covered so that they could not be affected by the meteorological conditions. The time periods were as follows: prints were visualised and copied immediately after leaving them, in 12 hours, in 24 hours and in 36 hours after leaving the experimental prints. As the result 176 papillae pattern prints were left on the surfaces if fruits and vegetables. 43 of them were recognised as valid for person identification. The third stage was performed in the room where the temperature varied from 21°C to 25°C. Experimental papillae pattern prints were left on the leaves of dandelion, apple tree, birch, plantain, clematis and bent-grass. Immediately after leaving the prints they were processed with black fingerprint powder and copied by white Mikrosil silicon casting material. As the result 13 papillae pattern prints were left on the surfaces of plant leaves. All of them were recognised as valid for person identification. Whereas, in the fourth stage plant leaves were exposed to the influence of meteorological conditions (air temperature varied from 28°C to 34°C, it was almost sunny, the slow wind, a bit rain) for time periods of 24 hours and 48 hours. As the result 65 papillae pattern prints were left on the surfaces of plant leaves. 11 of them were recognised as valid for person identification. The summary of the results obtained during the experiment and the analysis let to conclude that: it is possible to find, visualise and recover papillae pattern prints from the surfaces of fruits, vegetables and plant leaves by using powder method which can be used both on scene and under laboratory conditions; there is no set proportionality between number of prints left and prints valid for person identification; quality of prints is not always influenced by preservation time period of prints; meteorological conditions have essential influence on the quality of prints in the preservation time period of prints.